Genetic divergence in common bean genotypes from the IRAD gene bank: morpho-agronomic characteristics, fungal and bacterial disease resistance, and opportunities for genetic improvement - Kouam, Eric Bertrand; Djeugap-Fovo, Joseph; Meka-Sindje, Solange; Afsah, Nadia Mokia Mbinkar; Meyia, Arielle; Babagnack, Blaise Franky; Nouteka, Niky K. J.; Galani-Yamdeu, Joseph Hubert (Frontiers in Horticulture, 2023)
For successful plant breeding in any crop species, the importance of diversity in the available germplasm population is known and established. Thirty-two common bean (Phaseolus vulgaris) genotypes from IRAD genebank in Cameroon were evaluated for divergence in morpho-agronomic traits, fungal and bacterial disease resistance to assess the opportunity for genetic improvement of the crop. Trait associations were estimated using correlation coefficients and genotypes were classified into groups using cluster and principal component analysis. Seven qualitative and sixteen quantitative traits comprising growth, phenological, yield and disease variables were evaluated in this study. Qualitative markers revealed polymorphism among the 32 common bean genotypes. The number of phenotypic classes per character (Na) varied 2-18 with an average 5.14. Expected gene diversity (He) varied from 0.37 to 0.93 (mean = 0.56). The number of effective phenotypic class (Ne) was 1.82-14.22 with a mean of 3.85. An extensive range of variation was evident for majority of traits, highlighting their utility for characterizing common bean germplasm. Many qualitative traits including seed coat colour, seed shape and size, as well as some quantitative traits of economic importance including seed yield, were found to be highly variable within the collection with MAC55 genotype displaying the highest yield (32.65 g/plant). Four genotypes namely MAC55, BOA-5-1M6, FEB 192 and Banguem showed resistance to two main common bean diseases, angular leaf spot and common blight. Highly significant correlations were detected among several traits related to yield. High broadsense heritability was found for most quantitative traits. Two-dimensional principal component analysis as well as hierarchicalField Code Changed clustering grouped the analysed germplasm according to their phenotypic similitudes. The evidence of agro-morphological diversity in the present collection as well as the identification of discriminant characters between the available germplasm by the help of PCA analysis have significant implications for establishing breeding schemes in common bean.